Performing virtual and/or physical resource management for power management - RAJAMANI KARTHICK; WARE MALCOLM S; SWANBERG RANDAL C; NAYAR NARESH; RAWSON, III FREEMAN L; FRANCOIS CHRISTOPHER; FLOYD MICHAEL S (2013)
A mechanism is provided for directed resource folding for power management. The mechanism receives a set of static platform characteristics and a set of dynamic platform characteristics for a set of resources associated with the data processing system thereby forming characteristic information. The mechanism determines whether one or more conditions have been met for each resource in the set of resources using the characteristic information. Responsive to the one or more conditions being met, the mechanism performs a resource optimization to determine at least one of a first subset of resources in the set of resources to keep active and a second subset of resources in the set of resources to dynamically fold. Based on the resource optimization, the mechanism performs either a virtual resource optimization to optimally schedule the first subset of resources or a physical resource optimization to dynamically fold the second subset of resources.